The emotional value of arts-based initiatives: Strengthening the luxury brand–consumer relationship - Koronaki, Eirini; Kyrousi, Antigone G.; Panigyrakis, George G. (My University, 2018)
This paper discusses how Arts-Based Initiatives offered to consumers can function as a source of value creation. The conceptual model proposes that brand connoisseurs’ despite not being physically present in such initiatives, derive emotional value which positively affects brand loyalty through the mediating role of brand attachment. The findings of a study investigating how consumers respond to this emerging practice by luxury brands reported, largely confirm the relevant hypotheses. Relevant theoretical implications include the extension of previous conceptualizations of this practice and the contribution to understanding relevant consumer responses, while the findings also suggest that luxury brand managers can use Arts-Based Initiatives as a relationship-strengthening tool that transcends geographical barriers.
Keywords: Arts-based initiatives; Brand attachment; Brand loyalty; Luxury brands; Value creation